Administrative simplification and perception of quality of services of the Unit of Degrees and Titles in graduates - Anibal-Rivero, Pedro R. (2021)
Objective. Determine compliance with administrative simplification and the perception of the quality of services of the Unit of Degrees and Titles in graduates of Professional Schools of the National University Hermilio Valdizan (UNHEVAL) of Huánuco. Methods. The research was quantitative, explanatory level and the analysis-synthesis, inductive-deductive methods were used; The sample consisted of 85 graduates, stratified from the 27 professional careers. As techniques for data collection, the survey and documentary review were used; as instruments the cards and the questionnaire. We proceeded to tabulate the data and prepare tables and graphs to analyze the results. The design was non-experimental, transactional, descriptive and causal. Results. The results showed that the procedures in the Unit are cumbersome, repetitive, the established deadlines and times are not met, the graduates do not receive orientation and courteous treatment, which generates continuous claims and complaints, modern technology is not used; likewise, graduates perceive that the staff is not trained for the service. Conclusion. The Unit does not comply with administrative simplification, with unnecessary requirements, it lacks modern technology and infrastructure to provide a quality service, the staff lacks the skills to offer an efficient service, generating mistrust in the graduates who perceive the quality of the service as poor.